Job Growth and the Quality of Jobs in the U.S. Economy - Susan N. Houseman (W.E. Upjohn Institute for Employment Research, 1995)
During the 1980's employment grew rapidly in the United States, prompting many analysts to label the U.S. economy the great American job machine. But while aggregate employment increased rapidly during the 1980's, many did not benefit from the expansion. Among less educated prime-age males, unemployment rates rose and labor force participation rates declined sharply. Moreover, although job growth was high, many argued that the quality of American jobs as measured by wages, benefits, and job security deteriorated. The decline of jobs in the high-paying manufacturing sector and the growth of jobs in the low-paying services sector, the growth in part-time and temporary employment, and the general decline in real wages among less-educated, less-skilled workers have been presented as evidence of an erosion in job quality. The issue of job growth and job quality in the American economy has sparked extensive debate among policymakers and academics over the last decade. The aim of this paper is to critically examine the evidence on job growth and on wages and other indicators of job quality in the U.S. economy during the 1980's and 1990's. To place the American experience in perspective, selected comparisons are made to the experiences in other industrialized countries. The paper is divided into three main sections. In section 1, I look at employment growth in the United States during the 1980's and 1990's. I examine whether and to what extent employment growth was greater in the United States than in other industrialized countries and whether strong employment growth in the United States signaled a healthy economy. I compare the employment performance of the U.S. economy during the 1980's with that in other industrialized countries, and study the factors underlying the cross-country differences in employment growth: differences in the growth of the working age population, differences in the growth in labor force participation, and differences in the growth in unemployment. I also examine differences in the employment experiences across groups of workers defined by gender, education, and age within the United States. In addition, the relation between employment growth, productivity growth, and growth in per capita GDP in the United States and other industrialized countries during the 1980's is explored. Finally, trends in employment growth in the United States during the 1990's are discussed. In sections 2 and 3 of the paper, I examine whether and in what sense there is any evidence that the quality of jobs in the United States has declined. The literature pertaining to trends in the quality of jobs in the U.S. economy falls into at least two main categories: (1) studies of the wage, benefits, and job security characteristics of new jobs created; and (2) studies of trends in real wages, benefits, and earnings inequality. The latter deals with trends in new as well as existing jobs. In section 2 of the paper, I review evidence from several studies on the wage distribution of occupations and industries in which new employment was created during the 1980's and 1990's. I also look at trends in the growth of involuntary part-time employment and temporary employment, which are characterized by low wages, few benefits, and little job security. In section 3 of the paper, I present evidence on trends in wages and benefits across groups of workers and the growth of wage inequality in the United States during the 1980's and 1990's. I review evidence concerning the causes of the decline in real wages among less-educated workers and the growth in wage inequality in the United States. I also review evidence from studies of trends in real wages and wage inequality in other industrialized countries and discuss why trends abroad typically have differed from those in the United States. In section 4, I summarize the evidence on job growth and the quality of jobs in the United States during the 1980's and 1990's and discuss the implications for U.S. policy.
Additional information: A revised version of this paper appears in Labour, Special Issue, 1995, pp. S93-S124. Please cite the revised version.
Keywords: J0; J2; J6; 330; job; growth; quality; expansion; Houseman